2013
DOI: 10.1002/cncr.28491
|View full text |Cite
|
Sign up to set email alerts
|

Significant involvement of herpesvirus entry mediator in human esophageal squamous cell carcinoma

Abstract: BACKGROUND: Herpesvirus entry mediator (HVEM) is known to regulate immune response and to be expressed in several human malignancies. However, to the authors's knowledge, the precise role of HVEM in human cancer biology remains unknown. The objective of the current study was to clarify the clinical significance of HVEM in human esophageal squamous cell carcinoma as well as its in vivo functions. METHODS: HVEM expression was evaluated in 103 patients with esophageal squamous cell carcinoma to explore its clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 41 publications
(105 reference statements)
1
50
1
Order By: Relevance
“…11 High levels of HVEM expression in human esophageal squamous cell carcinoma are associated with significantly lower survival rates. 12 Similar results have been obtained in colorectal cancer, 13 hepatocellular carcinoma, 14 breast cancer, 15 ovarian serous adenocarcinoma, 16 clear renal cell carcinoma 17 and glioblastoma 18 . However, the problem is more complex, since high levels of HVEM expression were associated with improved cancer-specific survival in other tumor like pancreatic, ampullary, 19 and bladder cancer.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…11 High levels of HVEM expression in human esophageal squamous cell carcinoma are associated with significantly lower survival rates. 12 Similar results have been obtained in colorectal cancer, 13 hepatocellular carcinoma, 14 breast cancer, 15 ovarian serous adenocarcinoma, 16 clear renal cell carcinoma 17 and glioblastoma 18 . However, the problem is more complex, since high levels of HVEM expression were associated with improved cancer-specific survival in other tumor like pancreatic, ampullary, 19 and bladder cancer.…”
Section: Introductionsupporting
confidence: 61%
“…obtained in seven other solid tumors (esophageal squamous cell carcinoma, 12 colorectal cancer, 13 hepatocellular carcinoma, 14 breast cancer, 15 ovarian serous adenocarcinoma, 16 clear renal cell carcinoma 17 and glioblastoma 18 ), suggesting a role for HVEM in tumor progression.…”
Section: Discussionmentioning
confidence: 95%
“…The results are generally consistent with the high expression of HVEM in esophageal cancer, which was involved in tumor invasion and lymph node metastasis. 9 A previous study reported that soluble HVEM in the sera of gastric cancer patients was significantly higher than that of normal control, which was argued to be produced by ectodomain shedding rather than by simple secretion. 21 Another study found that HVEM was overexpressed in colorectal cancer tissues, being correlated with tumor invasion and pathological stage, but being inversely correlated with the presence of tumor-infiltrating T cells.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have shown that HVEM overexpression and gene polymorphisms can both be associated with malignancies such as colorectal cancer, melanoma, and breast cancer as well as haematopoietical malignancies (Table 3). Whilst its role in tumourigenesis has not been completely understood, recent studies demonstrate that high levels of HVEM expression on tumour cells is associated with unfavourable prognosis in patients with oesophageal squamous cell carcinoma (Migita et al., 2014). High levels of HVEM on these patients tumours' correlated with larger tumour size, lymph node metastasis and lower 5‐year survival rate.…”
Section: Inhibitory Receptors: Mechanism Of Action and Targeted Theramentioning
confidence: 99%
“…High levels of HVEM on these patients tumours' correlated with larger tumour size, lymph node metastasis and lower 5‐year survival rate. Of relevance, tumours expressing high levels of HVEM were also found to be poorly infiltrated by both CD4 + and CD8 + T cells (Migita et al., 2014). In human colorectal cancer HVEM expression was also inversely correlated with the presence of tumour‐infiltrating T cells (Inoue et al., 2015).…”
Section: Inhibitory Receptors: Mechanism Of Action and Targeted Theramentioning
confidence: 99%